Linkages between government spending, growth, and poverty in India and China - Fan, Shenggen (Cornell University, 2007)
The objective of this case study is to present a synthesis of the links between government spending— in areas such as agricultural research and development (R&D), irrigation, rural education, and infrastructure (including roads, electricity, and telecommunications)— and economic growth and poverty reduction in China and India. The findings of this case study are intended to help explain how government spending on key investments can help meet the broader policy goals of improved growth and reduction in poverty through various channels. The study, using a common framework, seeks to broaden and deepen understanding of the mechanisms through which government investment results in pro-poor economic growth.; The overall picture for public investment can be summarized as follows:; Using state-level data for India over time, the study found that many types of government spending have resulted in reductions in rural poverty, and most have also contributed to growth in agricultural productivity. Different kinds of spending, however, have different effects on poverty and productivity. Rural roads and agricultural research have the largest impact on agricultural growth and poverty reduction. Many investments in rainfed areas of eastern India offer the largest impact on rural poverty, but also contribute to higher growth in comparison with investments in the more-favored irrigated areas.; Using provincial data over time, the study shows that for China, government investment in agricultural R&D and rural education have had the largest impact on both growth and poverty reduction. To eliminate the remaining poverty in China, the government should place the highest priority on public investment in western China, where the majority of the poor reside, because the marginal returns to public investments, in terms of poverty reduction, are higher there than in other regions.; Your assignment is to recommend a public sector investment strategy for rural infrastructure to be considered by the government of one of the two countries discussed in this case.